Topical Effect of Pinneaple (Ananas comosus) Juice in Combustio Healing Process Measured by Granulation Process, Reepitelialisation and Angiogenesis - Azaria, Cherry; Achadiyani, Achadiyani; Farenia, Reni (Maranatha Christian University, 2017)
Skin protects the body from various trauma, such as high temperature trauma known ascombustio. Pineapple (Ananas comosus) contains lots of substances such as bromelain,antioxidants, and zinc shown to accelerated healing process in previous experiments. Aim ofthis research was to analize the effect of topical pinneaple juice application in combustiohealing process. The method was true experimental laboratory. Wistar ratsâ back skin wereinduced by 100 o C iron plat untill 2 nd degree combustio occured, then divided into two groups(n=20). The treatment group were given topical application of pinneaple juice, then the healingprocess were observed macroscopically and microscopically on day 0, 3, 7, and 14. The resultshowed better wound healing in treatment group on day 14. MANOVA test showed topicalapplication of pinneaple juice accelerated healing process (p=0.001). Treatment group showedbetter histological structure changes, as seen from better granulation tissue formed (p=0.003)and reepithelization (p=0,000), but not from angiogenesis (p=0.733). Conclusion, topicalapplication of pinneaple (Ananas comosus) juice accelerated healing process in 2 nd grade ofcombustio animal model measured by granulation maturation process and reepithelizationprocess, but has no effect on angiogenesis.Keywords : Ananas comosus juice, 2 nd degree combustio, granulation tissue, reepitelisation,angiogenesis.